Pengaruh Layanan Samsat Keliling, E-Samsat Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor: Studi Kasus pada Kantor Samsat Cianjur - Muhammad Dian Maulana; Dwi Septiani (Jurnal Akuntansi, 2022)
This study aims to determine the effect of Samsat Keliling Services, E-Samsat and Tax Sanctions on Motor Vehicle Taxpayer Compliance on Motor Vehicle Taxpayers in Cianjur Regency. The method used in this research is multiple linear regression analysis method. this type of research is quantitative. The data used in this research is primary data. The population in this study were 459,151 motor vehicle taxpayers. The sampling method used the slovin formula so that 100 respondents were obtained and the sampling technique used was random sampling technique. Processing of data using Microsoft Office Excel and SPSS version 26 program then the data was analyzed by descriptive statistical test, data quality test, classical assumption test, coefficient of determination test (R2), F statistic test and t statistic test. Based on the results of simultaneous hypothesis testing (F test) the service variables of samsat keliling services, e-samsat and tax sanctions affect the compliance of motorized vehicle taxpayers. The results of the partial hypothesis test show that samsat keliling services and tax sanctions didn’n have effect on motor vehicle taxpayer compliance, while e-samsat has no effect on motor vehicle taxpayer compliance.